1974
DOI: 10.1093/jn/104.7.819
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Gluten and Casein Diets on Rat Liver HMP Shunt Dehydrogenases

Abstract: The effect of diets containing as their protein component wheat gluten or casein, fed ad libitum to adult male rats for 1 to 6 days, after 6 days of protein deprivation, on the liver levels of glucose-6-phosphate dehydrogenase (G8PD) and 6-phosphogluconate dehydrogenase (6PGD) were studied. In rats fed the gluten diet the values of body weight gain, liver size, liver protein, liver xanthine oxidase, G«PD and 6PGD activities were lower in comparison with rats fed the casein diet. Amino acid supplements to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1974
1974
1979
1979

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…In table 3 the levels of plasma insulin are shown. As has previously been found (21)(22)(23)(24), rats fed the gluten diet for 6 days had lower body weight gain, smaller liver and less liver protein than rats fed the casein diet. These effects were overcome by adding a suffi cient amount of Lys and Thr to the gluten.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…In table 3 the levels of plasma insulin are shown. As has previously been found (21)(22)(23)(24), rats fed the gluten diet for 6 days had lower body weight gain, smaller liver and less liver protein than rats fed the casein diet. These effects were overcome by adding a suffi cient amount of Lys and Thr to the gluten.…”
Section: Resultssupporting
confidence: 82%
“…Adult male WAG rats (240 to 340 g) were caged from weaning at constant tem perature (23°) and had free access to a stock diet.2 At the beginning of the experi ment, the animals were housed individually and fed a protein-free diet for 6 days; sub sequently some were fed for 4 days and others for 6 days a balanced diet contain ing, as its exclusive nitrogen source, casein or wheat gluten with or without \% L-lysine-HCL and 0.40% L-threonine. In order to equalize the essential fatty acid content of the casein-and gluten diet, the former was supplemented at the expense of starch (w/w) with 1.2% corn oil and 0.019% methyl-linolenate.3 The composi tion of the diets has been described in a preceding paper (23). At the end of refeeding the rats were anaesthetized with sodium pentobarbital * and the abdomen was opened in order to extract the blood from the cava inferior and to remove the liver and the epididymal pads.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous papers it has been shown that liver levels of both hexose monophosphate (HMP) shunt dehydrogenases are higher when casein replaces wheat gluten as the dietary protein component (1)(2)(3).…”
mentioning
confidence: 99%